Burdens of Proof : Faith, Doubt, and Identity in Autobiography - Egan, Susanna, 1942- (Book collections on Project MUSE., 2011)
Examines autobiographical imposture as a recent phenomenon with deep and complex historical roots, asking how and why it occurs and what it tells us about the cultures in which it arises. This title offers the analysis of fraud in autobiography.